Using online field surveys in e-business research: reflections on a referent study. (2015) - Cui, Xiling; Zhou, Qiang; Liu, Libo
The growing popularity of mixed-methods approaches to information systems (ISs) research calls for further exploration of research design strategies. We review the advantages and disadvantages of field studies and surveys in e-business studies, and integrate these two methods to produce the online field survey method. We argue that online field surveys offer an effective means of conducting e-business research because they balance the strengths and weaknesses of research designs based solely on field studies or surveys, providing e-business researchers with more robust findings. Next, we empirically demonstrate an online field survey in the context of an online-auction study in which psychological factors of online purchasers are evaluated. After evaluating our referent study, we provide recommendations for future e-business research. This study contributes to the existing literature on both e-business and methodology by providing an effective research design. It also offers valuable insights into IS research and practice.